Molecular genetic methods in the diagnosis of myelodysplastic syndromes. A review - Lukackova, Renata; Gerykova Bujalkova, Maria; Majerova, Lubica; Mladosievicova, Beata (Biomedical papers, 2014)
Background: Myelodysplastic syndromes (MDS) represent a heterogeneous group of premalignant hematologic disorders characterized by ineffective hematopoiesis, peripheral blood cytopenias and increased risk of progression to acute leukemia. Cytogenetic analysis still plays a central role in the diagnosis of MDS, as clonal chromosomal abnormalities are observed in 30-50% of MDS patients. Despite their technical limitations, standard karyotyping and fluorescence in situ hybridization (FISH) are routinely used for identifying recurrent chromosomal rearrangements. However, using this approach means that submicroscopic and not targeted chromosomal aberrations, as well as somatic mutations and epigenetic changes remain largely undetected.Methods and Results: Introduction of methods for the analysis of copy-number variations (CNV), including array-based technologies and Multiplex ligation-dependent probe amplification (MLPA) has provided novel insights into the molecular pathogenesis of MDS and considerably extended possibilities for genetic laboratory testing. Several novel molecular markers have been discovered and used for diagnosis and prognostic evaluation of patients with MDS. At present, mutational analysis is not routinely performed, as the clinical significance of somatic mutations in MDS has only begun to emerge. However, recently introduced Next-generation sequencing (NGS) technologies could help to elucidate the relationship between chromosomal and molecular aberrations in MDS and lead to further improvement in its diagnosis.Conclusion: This review focuses on the advantages, limitations, clinical applications and future perspectives of three molecular methods (array-based analysis, MLPA and NGS) currently used in genetic testing and/ or translational research of MDS. In conclusion, a brief summary for clinicians from the routine diagnostic point of view is given.
Keywords: myelodyplastic syndromes; aCGH; SNP array; multiplex ligation-dependent probe amplification; CNV (copy-number variations); NGS; somatic mutations; prognostic markers; genetic testing